2010
DOI: 10.1002/jmv.21846
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B in the genotype H‐infected Nahuas and Huichol native Mexican population

Abstract: Mexico is considered to be a low endemic country for HBV infection. However, a high anti-HBc against a low hepatitis B surface antigen (HBsAg) seroprevalence is the reported characteristic of native Mexicans. HBV diagnosis and genotype distribution was examined in native populations (Nahuas and Huichol, n = 306), and compared to a non-native population (Mestizos, n = 17). Overall, 6% of the natives were positive for HBsAg and 33% had detectable anti-HBc. HBsAg prevalence was lower in Nahuas compared to Huichol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
84
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 41 publications
7
84
1
3
Order By: Relevance
“…Subjects -A previous, cross-sectional study conducted by our group revealed that OHB genotype H infection is common among members of the Nahua community (Roman et al 2010). In the present study, 41 sera samples from Nahua subjects were retrospectively analysed.…”
Section: Subjects Materials and Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…Subjects -A previous, cross-sectional study conducted by our group revealed that OHB genotype H infection is common among members of the Nahua community (Roman et al 2010). In the present study, 41 sera samples from Nahua subjects were retrospectively analysed.…”
Section: Subjects Materials and Methodsmentioning
confidence: 98%
“…We have shown previously that OHB genotype H is common among the ethnic Nahua population (Roman et al 2010). Additionally, Mexico has been reported to be a low endemic area for HBV and there is a low association between HBV infection and HCC reported in the country (Roman et al 2010). These data may indicate that the natural course of liver diseases in the native populations of Mexico may be different from what is described in high endemic areas for HBV infection.…”
mentioning
confidence: 84%
See 3 more Smart Citations